Isolation and screening of azo dye reactive violet 5R degrading bacteria from textile sludge - Ahmed, Hasan Hasnaeen (2016)
This thesis report is submitted in partial fulfillment of the requirement for the degree of Bachelor of Science in Biotechnology, 2016